Navigating the 'space between' the Black/White binary: a call for Jewish multicultural inclusion. Issue 2 (3rd April 2019) - Rubin, Daniel Ian
ABSTRACT: In the twenty-first century, diversity and multicultural analysis of race often falls along a Black/White binary paradigm. Therefore, those who are perceived to be White are often left out of the discussion of diversity and multicultural education (DME) in the United States. This absence is particularly true for American Jews of Ashkenazi descent. In academic circles today, the notion of 'Whiteness' is often used as a determining factor for overlooking antisemitism while addressing issues of racism aimed at other racial and ethnic groups in the United States. Data show that acts of antisemitism continues to rise in the U.S., especially on college campuses. Due to a lack of acknowledgment in the university classroom, Jews continue to be overlooked in multicultural academic thought, which can have wide-ranging consequences for Jews and non-Jews alike.